ANALISIS PENGELOLAAN DANA DESA SEBAGAI REALISASI SALAH SATU TUJUAN PROGRAM NAWACITA “MEMBANGUN INDONESIA DARI PINGGIRAN” DI KECAMATAN BENER KABUPATEN PURWOREJO TAHUN 2016 - Ria Nurpuspita; Sudati Nur Sarfiah; Emma Dwi Ratnasari (DINAMIC : Directory Journal of Economic, 2019)
The government implemented the Village Fund program in order to develop the economy of the small region. The allocation of village funds is expected to increase equitable development of village welfare through improving public services in the village, advancing the village economy, overcoming  the  development  gap  between  villages  and  strengthening  village  communities  as subjects of development. So in this study a research title is "Analysis of Village Fund Management as One of the Objectives of the Nawacita Program" Building Indonesia from the Outskirts "in the District of Bener, Purworejo Regency in 2016". Village Fund (DD) is a fund given to the Village Government to be used to improve community service facilities, institutional and village infrastructure needed and prioritized by the community, whose utilization and administration of management is carried out and can be accounted for by the Village Head. The priority of using Village Funds is to fund programs or activities in the field of rural development and empowerment of rural communities. This research was conducted in Bener District, Purworejo Regency. This study aims to: (1) To find out the contribution of village funds to the development of rural areas in Bener sub-district, Purworejo district. (2) To analyze the use of village funds by the village government in Bener sub-district, Purworejo district. (3) To find out obstacles in rural development related to village funds. With this result, efforts must be made especially for village governments in Bener District to pay more attention to community involvement in managing Village Funds.